BETAINE CONTENT IN RAW COW AND SHEEP MILK - Zivkovic, Jelena; Trutić, Nataša; Sunarić, Slavica; Živanović, Slavoljub; Jovanović, Tatjana; Kocić, Gordana; Pavlović, Radmila (Acta medicae Medianae, 2022)
Betaine (trimethylglycine) exists at a physiological pH value in a zwitterionic form. It acts as a methyl group donor, an osmolyte, and a lipotropic agent. Although this micronutrient is a valuable ingredient of a healthy diet, there is limited data on its content in various foods. The aim of this study was to determine the betaine content in raw, unprocessed cow and sheep milk from household farms in southeastern Serbia. The content of fat and protein in raw cow milk was (4.20 ± 0.38%) and (3.25 ± 0.12%), respectively. Furthermore, the content of fat and protein in raw sheep milk was (6.67 ± 0.33%) and (5.58 ± 0.16%), respectively. The content of betaine in raw cow and sheep milk was (7.51 ± 0.66 mg/l) and (15.68 ± 3.52 mg/l), respectively. Given the importance of betaine as a significant micronutrient, its twice as high content as in cow milk contributes to the high nutritional value of sheep milk.
Keywords: betaine, cow milk, sheep milk, HPLC method